A framework for international monetary reform? - G. Zis (Intereconomics, 1982)
The European Monetary System (EMS) has, so far, proved to be a success. The regional approach to the promotion of monetary stability, in terms of both more predictable exchange rates and a reduction in inflation, is the only option available to Europe as attempts to create a new international monetary system without an inflation bias and national initiatives to reduce inflation have failed. Can the EMS, building on its success, so evolve as to facllitate the reform of the international monetary system and the permanent reduction of inflation?
Keywords: 330; European Monetary System